TRUSTING THE SURVIVORS TO RECONSTRUCT THEIR OWN SHELTER: CHALLENGES, CONSTRAINT AND ADVANTAGES LESSON LEARNED FROM UN HABITAT’S POST DISASTER RECONSTRUCTION PROJECT IN ACEH, INDONESIA1 - Asnawi Manaf (TATALOKA, 2011)
In recent decades, the community participation process in development activities has been widely recognized as the most effective way to help communities, particularly the poor, to fulfill their basic needs. This approach has been practiced not only in normal situations but also in the emergency ones such as in the post earthquake disasters in Yogyakarta, Central Java and North Sumatra, and in the post tsunami disaster in Nanggroe Aceh Darussalam, Indonesia. This paper examines the practice of community participation in the post tsunami disaster recovery project in Nanggroe Aceh Darussalam conducted by the United Nations Human Settlements Programme (UN-HABITAT) and outlines chal-lenges, constraints and advantages faced in the implementation of the approach. This research em-ployed a qualitative method (participatory action research) and focused on a case study in the Geunteng Village of Pidie District, Nanggroe Aceh Darussalam. This research found that ensuring the quality of construction organized by the community in the limited timeframe and in the chaotic post disaster cir-cumstances is the most challenging issue in implementing such an approach. However, this paper ar-gues that it has potential to mobilize social resources available in the community, to increase the value of output, to enhance transparency and democracy, to empower community bargaining to the external stakeholders and to improve the sensitivity of the local contexts culturally and socio-economically.